Patient and healthcare provider experience and perceptions of a preoperative rehabilitation class for lumbar discectomy: A qualitative study. (April 2023) - Alsaif, Hanan; Goodwin, Peter C.; Callaghan, Michael J.; Sudell, Lindsay; O'Neill, Terence W.; Yeowell, Gillian
Abstract: Background: Lumbar disc disease is a leading cause of low back pain. Lumbar discectomy (LD) may be indicated if symptoms are not managed conservatively. Rehabilitation has traditionally been delivered postoperatively; however, there is increasing delivery preoperatively. There are few data concerning perceptions and experiences of preoperative rehabilitation. Exploring experiences of preoperative rehabilitation may help in the development and delivery of effective care for patients. Objectives: To develop an understanding of patient and healthcare provider (HCP) experiences, perspectives and preferences of preoperative LD rehabilitation, including why patients do not attend. Design: A qualitative interpretive approach using focus groups and individual interviews. Methods: Data were collected from; a) patients listed for surgery and attended the preoperative rehabilitation (October 2019 to March 2020), b) patients listed for surgery but did not attend rehabilitation, and c) HCPs involved in the delivery of rehabilitation. Data were transcribed verbatim and analysed using thematic analysis. Results/findings: Twenty participants were included, twelve patients and eight HCPs. The preoperative class was a valuable service for both patients and HCPs. It provided a solution to staffing and time pressures. It provided the required education and exercise content helping the patients along their surgery pathway. Travel distance, transportation links, parking difficulty and cost, lack of knowledge about the class aims, and previous negative experiences were barriers to patient attendance. Conclusions: For most patients and HCPs, the preoperative class was valuable. Addressing the challenges and barriers could improve attendance. Future research should focus on management of patient expectations and preferences preoperatively. Highlights: Preoperative rehabilitation was valuable to patients and healthcare providers. It provided a solution to staffing and time pressures. It provided the required patient education and exercise content. Travel, lack of clear aim and negative experiences were barriers to attendance.